Continuous "Snowing" Thermotherapeutic Graphene. Issue 26 (19th May 2020) - Sun, Yangyong; Chen, Zengzhen; Gong, Huiping; Li, Xueqiao; Gao, Zhenfei; Xu, Shichen; Han, Xiaodong; Han, Bing; Meng, Xianwei; Zhang, Jin
Abstract: Finding the best applications of graphene, and the continuous and scalable preparation of graphene with high quality and high purity, are still two major challenges. Herein, a "pulse‐etched" microwave‐induced "snowing" (PEMIS) process is developed for continuous and scalable preparation of high‐quality and high‐purity graphene directly in the gas phase, which is found to have excellent thermotherapeutic effects. The obtained graphene exhibits small size (≈180 nm), high quality, low oxygen content, and high purity, together with a high gas–solid conversion efficiency of ≈10.46%. Considering the intrinsic characteristics of this high‐purity and small‐sized biocompatible graphene, in particular the low‐frequency microwave absorption property as well as the good thermal transformation ability, a graphene‐based combination therapeutic system is demonstrated for microwave thermal therapy (MTT) for the first time, exhibiting a high tumor ablation rate of ≈86.7%. This is different from the principle of ions vibrating in a confined space used by current MTT sensitization materials. Not limited to this application, it is foreseen that this PEMIS‐based high‐quality graphene will allow the search for further suitable applications of graphene. Abstract : A continuous and scalable "snowing" process for preparation of graphene with high quality and high purity is demonstrated. Based on the intrinsic characteristics of this graphene, in particular the low‐frequency microwave absorption property and good thermal transformation ability, a graphene‐based combination therapeutic system for microwave thermal therapy is achieved.